Justice-Oriented Reform of Regulations Protecting Land Deed Officials in Land Title Transfers - Mashdurohatun, Anis; Erawati, Wahyu Ririn; Yuniarti, Endang; Andaryanti, Yuni; Aquino, Thomas (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This research aims to examine and propose justice-oriented reforms to strengthen legal protections for Land Deed Officials (PPAT) in Indonesia, focusing on the gaps and limitations in existing regulations such as Government Regulation No. 24 of 1997 and subsequent amendments. The study addresses the challenges faced by Land Deed Officials, including criminalization, professional risks, and inadequate procedural safeguards, and aligns the proposed reforms with the foundational principles of Pancasila. The research employs a juridical-sociological methodology, combining doctrinal analysis and field data collection through interviews and questionnaires with Land Deed Officials and related stakeholders. Comparative legal analysis is also conducted, referencing practices in jurisdictions such as the Netherlands, France, and the United States, to derive best practices for enhancing legal protections. Key findings indicate that current regulations lack explicit provisions to shield Land Deed Officials from liability for actions performed in good faith, fail to provide mechanisms for compensation in cases of wrongful accusations, and do not empower supervisory bodies such as the Supervisory and Advisory Board (MPPD) with adequate authority. The study further reveals that the integration of digital tools like electronic signatures and blockchain can improve procedural efficiency but requires comprehensive training and robust legal frameworks. The study concludes that justice-oriented reforms should incorporate explicit protections for Land Deed Officials, including immunity for lawful actions, professional liability insurance, and enhanced supervisory powers for Supervisory and Advisory Board. These reforms must align with Pancasila principles to ensure fairness, legal certainty, and human dignity. By addressing these systemic gaps, the proposed framework aims to bolster public trust, protect Land Deed Officials, and enhance the integrity of Indonesia’s land administration system, fostering equitable and transparent land title transfer processes.